Response of pea genotypes to seed infection by Ascochyta blight fungi. - Marcinkowska, Joanna; Boros, Lech; Wawer, Anna (Plant Breeding and Seed Science, 2009)
Seeds collected from 10 genotypes of Pisum sativum of both foliage type, inoculated in field by Mycosphaerella pinodes and Phoma pinodella, were evaluated for incidence of fungi responsible for ascochyta blight. Also seed germination and contamination by other fungi were considered. Surface sterilized seeds were plated on Coon agar medium. A sample contains 50 seeds. Data were taken after 8 days of incubation. Frequency of species occurrence depended not only on characters of genotypes, weather conditions during 1998-2001, but on inoculation treatment. Clear response between genotypes to tested factors was noted. Seeds of normal leaved line 344/87/3 and cv. Rubin were the most inhabited by all fungi, and germinated very poorly. Seeds of eight genotypes, including cvs: Kwestor, Agra, Miko, were less infected and better germinated...